Extended-spectrum beta-lactamase Escherichia coli and Klebsiella pneumoniae urinary tract infections. (17th December 2020) - Vachvanichsanong, P.; McNeil, E. B.; Dissaneewate, P.
Abstract: The prevalence of extended- spectrum beta- lactamase (ESBL)-producing Escherichia coli and Klebsiella pneumoniae urinary tract infections (UTIs) is increasing worldwide. We investigated the prevalence, clinical findings, impact and risk factors of ESBL E. coli / K. pneumoniae UTI through a retrospective review of the medical records of children with UTI aged <15 years admitted to Prince of Songkla University Hospital, Thailand over 10 years (2004–2013). Thirty-seven boys and 46 girls had ESBL-positive isolates in 102 UTI episodes, compared with 85 boys and 103 girls with non-ESBL isolates in 222 UTI episodes. The age of presentation and gender were not significantly different between the two groups. The prevalence of ESBL rose between 2004 and 2008 before plateauing at around 30–40% per year, with a significant difference between first and recurrent UTI episodes of 27.3% and 46.5%, respectively ( P = 0.003). Fever prior to UTI diagnosis was found in 78.4% of episodes in the non-ESBL group and 61.8% of episodes in the ESBL group ( P = 0.003). Multivariate analysis indicated that children without fever (odds ratio (OR) 2.14, 95% confidence interval (CI) 1.23–3.74) and those with recurrent UTI (OR 2.67, 95% CI 1.37–5.19) were more likely to yield ESBL on culture. Congenital anomalies of the kidney and urinary tract were not linked to the presence of ESBL UTI. In conclusion, ESBL producers represented one-third of E. coli / K. pneumoniae UTI episodes but neither clinical condition nor imaging studies were predictive of ESBL infections. Recurrent UTI was the sole independent risk factor identified.